2015
DOI: 10.1021/acs.organomet.5b00135
|View full text |Cite
|
Sign up to set email alerts
|

The Gilded Edge in Acetylenic Scaffolding II: A Computational Study of the Transmetalation Processes Involved in Palladium-Catalyzed Cross-Couplings of Gold(I) Acetylides

Abstract: The palladium-catalyzed cross-coupling reaction between phosphine-gold­(I) acetylides and aryl iodides has recently proven as a convenient alternative to the standard Sonogashira reaction, which instead employs terminal alkynes as substrates. This alternative reaction does not require the presence of an amine base, but still, however, requires a copper cocatalyst (CuI). In this theoretical work we have investigated the possible roles that this copper catalyst may play. Three transmetalation pathways can be ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Penta-1,3-diyn-3-one presents an example of one such unstable compound, which is difficult to handle. 15 A protodesilylation of its trimethylsilyl-protected precursor 18 (shown in Scheme 8) followed by treatment with iodobenzene (19) under Sonogashira conditions has been carried out in the author's laboratory, but none of the desired Sonogashira coupling product was obtained. 16 However, converting 18 into the gold species 20 (isolated in high yield) 16,17 and employing this compound as a substrate in the Sonogashira coupling with 19 gave the desired product 21 (Scheme 8).…”
Section: Scheme 7 Chemoselective Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Penta-1,3-diyn-3-one presents an example of one such unstable compound, which is difficult to handle. 15 A protodesilylation of its trimethylsilyl-protected precursor 18 (shown in Scheme 8) followed by treatment with iodobenzene (19) under Sonogashira conditions has been carried out in the author's laboratory, but none of the desired Sonogashira coupling product was obtained. 16 However, converting 18 into the gold species 20 (isolated in high yield) 16,17 and employing this compound as a substrate in the Sonogashira coupling with 19 gave the desired product 21 (Scheme 8).…”
Section: Scheme 7 Chemoselective Couplingmentioning
confidence: 99%
“…As Cu(I) is required in order to run the coupling reaction at room temperature, it seems that either route (ii) or (iii) is in play. A detailed computational study 19 suggests that route (ii) is the most viable, involving intermediates as shown in Scheme 9. For computational convenience, the PPh 3 ligands were exchanged for PMe 3 ligands.…”
Section: Transmetalation Step -Mechanistic Insightmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] The transmetalation reaction has been studied in some cases by computational methods, but experimental quantitative data are scarce. [29][30][31][32][33] In 2012 we reported a kinetic and computational study on the Rf/Cl exchange (transmetalation) between [PdRf2L2] and [AuClL] (L = AsPh3). 29 In that work we proposed that [AuClL], acting as "incoming ligand", substituted one L ligand at the palladium complex; at that step the transition state displayed a Pd-Au interaction.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, many examples of coupling reactions involving R-for-X Pd/Au transmetalations have been reported, in which organogold complexes participate as stoichiometric reagents, or are used as cocatalyst. The transmetalation reaction has been studied in some cases by computational methods, but quantitative experimental data are scarce. In 2012, we reported a kinetic and computational study on the Rf/Cl exchange (transmetalation) between [PdRf 2 L 2 ] and [AuClL] (L = AsPh 3 ) . In that work, we proposed that [AuClL], acting as “incoming ligand”, substituted one L ligand at the palladium complex; at that step, the transition state displayed a Pd–Au interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation